A proposal for a new classification of "unfavorable risk criteria" in patients with stage I endometrial cancer. Issue 7 (September 2019) - Li, Richard; Shinde, Ashwin; Han, Ernest; Lee, Stephen; Beriwal, Sushil; Harkenrider, Matthew; Kamrava, Mitchell; Chen, Yi-Jen; Glaser, Scott
Abstract : Background: Randomized trials describe differing sets of high–intermediate risk criteria. Objective: To use the National Cancer Database to compare the impact of radiation therapy in patients with stage I endometrial cancer meeting different criteria, and define a classification of "unfavorable risk." Methods: Patients with stage I endometrial cancer between January 2010 and December 2014 were identified in the National Cancer Database and stratified into two cohorts: (1) patients meeting Gynecologic Oncology Group (GOG)-99 criteria only for high–intermediate risk, but not Post-Operative Radiation Therapy in Endometrial Carcinoma (PORTEC)-1 criteria and (2) those meeting PORTEC-1 criteria only. High-risk stage I patients with both FIGO stage IB (under FIGO 2009 staging) and grade 3 disease were excluded. In each cohort, propensity score-matched survival analyses were performed. Based on these analyses, we propose a new classification of unfavorable risk. We then analyzed the association of adjuvant radiation with survival, stratified by this classification. Results: We identified 117, 272 patients with stage I endometrial cancer. Of these, 11, 207 patients met GOG-99 criteria only and 5, 920 patients met PORTEC-1 criteria only. After propensity score matching, adjuvant radiation therapy improved survival (HR=0.73; 95% CI 0.60 to 0.89; p=0.002) in the GOG-99 only cohort. However, there was no benefit of adjuvant radiation (HR=0.89; 95% CI 0.69 to 1.14; p=0.355) in the PORTEC-1 only cohort. We, therefore, defined unfavorable risk stage I endometrial cancer as two or more of the following risk factors: lymphovascular invasion, age ≥70, grade 2–3 disease, and FIGO stage IB. Adjuvant radiation improved survival in stage I patients with adverse risk factors (HR=0.74; 95% CI 0.68 to 0.80; p<0.001), but not in other stage I patients (HR=1.02; 95% CI 0.91 to 1.15; p=0.710; p interaction <0.001). Conclusion: Our study showed that adjuvant radiation was associated with an overall survival benefit in patients meeting GOG-99 criteria only; however, no survival benefit was seen in patients meeting PORTEC-1 criteria only. We propose a definition of unfavorable risk stage I endometrial cancer: ≥2 risk factors from among lymphovascular invasion, age ≥70, grade 2–3 disease, and FIGO stage IB disease.